KONFLIK PANDANGAN MASYARAKAT JEPANG TERHADAP KEKUATAN TERCERMIN DALAM SERIAL KAMEN RIDER GAIM - Daniel Hermawan; Nicco Handaya (Universitas Negeri Surabaya, 2020)
This study will compare two different opinions toward military power between Sakuraba Kouta and Kumon Kaito in the Japanese Television series Kamen Rider Gaim. The two opinions represent two arguments that exist among Japanese society toward the existence of military power. The research uses a qualitative method as the approach of study. We compare the dialogue between the two characters and analyze it using the semiotic theory. The results show that there is two different ideas about military power represented by the ideology brought by Sakuraba Kouta and Kumon Kaito. Sakuraba Kouta represent the ideology of people against the military power while Kumon Kaito represent the ideology of people supporting the military power.